STUDY ON SUPPLY CHAIN MANAGEMENT - Hinge, Arya Santosh; Shewale, Bhojraj; Sharma Padroo, Bhawna (International Journal of Research -GRANTHAALAYAH, 2025)
The supply chain is the backbone of every business system, connecting manufacturers, suppliers, warehouses, distributors, retailers, and customers through a network of activities, information, and physical goods. As global markets grow increasingly interdependent, the need for efficient supply chain management has become more critical than ever. This research paper provides a deeply detailed and comprehensive analysis of the modern supply chain, expanding across definitions, structures, theoretical foundations, technological advancements, and real-world challenges. Through extensive review of academic literature, industry reports, and conceptual analysis, this paper explores how supply chain’s function, where they fail, and how companies can optimize their networks to reduce cost, improve speed, and enhance customer satisfaction. Visual tools such as charts, graphs, and tables add clarity to the findings and help identify patterns. The study ultimately concludes that a highly efficient supply chain requires collaboration, technological integration, transparent communication, and continuous performance evaluation. Practical recommendations are offered to help companies design a resilient, flexible, and future-ready supply chain capable of meeting the demands of evolving global markets.